2021
DOI: 10.1186/s12909-021-02725-5
|View full text |Cite
|
Sign up to set email alerts
|

A physician assistant entry-level doctoral degree: more harm than good?

Abstract: Background As most health professions in the United States have adopted clinical or practice doctorates, there has been an ongoing debate on whether physician assistants (PAs) should transition from a master’s to a doctorate as the terminal degree. The authors examined perceived risks, benefits and impact of transitioning to an entry-level PA doctoral degree. Methods A multi-prong, mixed-methods approach was used that included a literature review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 20 publications
(24 reference statements)
5
41
0
Order By: Relevance
“…Using a randomized sample of 1,500 American PAs, Ohlemeier and Muma (2008) conducted a cross-sectional study investigating perceptions of the entry-level doctoral degree of practicing PAs and found that the majority of the respondents did not support moving toward an entry-level doctorate for the PA profession [9]. Similar ndings were also reported in subsequent studies [10][11][12][13][14]. Consequently, the national PA organizations such as AAPA and PAEA have opposed several motions to adopt the entry-level terminal doctoral degree for PAs due to increased debt burden and potential adverse impact on the diversity of the workforce [15].…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Using a randomized sample of 1,500 American PAs, Ohlemeier and Muma (2008) conducted a cross-sectional study investigating perceptions of the entry-level doctoral degree of practicing PAs and found that the majority of the respondents did not support moving toward an entry-level doctorate for the PA profession [9]. Similar ndings were also reported in subsequent studies [10][11][12][13][14]. Consequently, the national PA organizations such as AAPA and PAEA have opposed several motions to adopt the entry-level terminal doctoral degree for PAs due to increased debt burden and potential adverse impact on the diversity of the workforce [15].…”
Section: Introductionmentioning
confidence: 52%
“…As the health care milieu continues to change, the quest for doctoral education for PAs has continued at various levels. As of 2022, about 11 institutions have established post-professional programs such as Doctor of Medical Science [6, 7,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used in this study is part of large study exploring perceived benefits and impacts of an entry-level PA doctoral degree. Detailed study and data collection procedures have been previously described [ 12 ]. This study was approved by the Institutional Review Board (IRB) of the University of Maryland Baltimore.…”
Section: Methodsmentioning
confidence: 99%
“…38 participants who participated in the semi-structured interviews included 19 PA association leaders and members (50%), nine PA program directors and faulty (24%), six non-PA academic leaders (16%), two physicians (5%), and two employers (5%). Sample characteristics were previously described in detail [ 12 ]. Based on the findings from the interprofessional literature review, a semi-structured interview guide consisting of 11 items was developed to assess feasibility, benefits, and risks as well as the impact of an entry-level PA doctorate degree.…”
Section: Methodsmentioning
confidence: 99%